A New, Simple, and General Synthesis of N-Oxides of Iodopyridines and Iodoquinolines via the Diazotization–Iodination of Heterocyclic Amino N-Oxides in the Presence of p-Toluenesulfonic Acid in Water; Synthesis; Vol. 50, iss. 6 - Krasnokutskaya E. A . Elena Aleksandrovna (2018, 2018)
Title screen